A knowledge gap model for improving service quality of international distribution centers. Issue 4 (December 2016) - Huang, Show-Hui S; Hsu, Wen-Kai K
Abstract The purpose of this article is to examine the knowledge gap in service quality of international distribution centers (IDCs). The service requirement attributes (SRAs) of IDCs are first investigated from both the perspective of IDC users and IDC operators. Next, a fuzzy AHP approach is constructed to measure the weights of the SRAs. On the basis of these weights, a Knowledge Gap Model (KGM) is further proposed to improve the service quality of IDCs. Finally, the IDCs in Taiwan are empirically examined to validate the model. Results indentify 5 SRAs with negative knowledge gaps and 10 SRAs with positive knowledge gaps. On the basis of these results, some practical policies of resource reallocation for IDC operators are suggested. The KGM provides a methodology for relevant studies on service quality gaps. Furthermore, the empirical results can provide practical information for IDC operators to improve service quality efficiently, such as raising the turnaround rate of storage space, enhancing the professional capability and service attitudes of staff, and utilizing information systems.